2019
DOI: 10.1007/s40820-019-0322-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress on Zinc-Ion Rechargeable Batteries

Abstract: HIGHLIGHTS• The recent progress about zinc-ion batteries was systematically summarized in detail, including the merits and limits of aqueous and nonaqueous electrolytes, various cathode materials, zinc anode, and solid-state zinc-ion batteries.• Current challenges and perspectives to future research directions are also provided. ABSTRACT The increasing demands for environmentally friendly grid-scale electric energy storage devices with high energy density and low cost have stimulated the rapid development of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
136
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(140 citation statements)
references
References 135 publications
2
136
0
2
Order By: Relevance
“…Furthermore, its high theoretical specific capacity of 819 mAh g −1 , low redox potential of Zn/Zn 2+ (−0.76 V vs standard hydrogen electrode), and its low cost have captured significant research interest as one of the most promising battery technologies. [ 15–19 ] While much can be celebrated due to these attractive properties, ZIB research is still severely plagued with the limited selection of materials that can demonstrate reversible Zn 2+ storage after prolonged cycling. [ 20–22 ] This is especially crucial as the cathode is arguably one of the most important components in the ZIB, which can significantly influence the overall electrochemical performance of the ZIB.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its high theoretical specific capacity of 819 mAh g −1 , low redox potential of Zn/Zn 2+ (−0.76 V vs standard hydrogen electrode), and its low cost have captured significant research interest as one of the most promising battery technologies. [ 15–19 ] While much can be celebrated due to these attractive properties, ZIB research is still severely plagued with the limited selection of materials that can demonstrate reversible Zn 2+ storage after prolonged cycling. [ 20–22 ] This is especially crucial as the cathode is arguably one of the most important components in the ZIB, which can significantly influence the overall electrochemical performance of the ZIB.…”
Section: Introductionmentioning
confidence: 99%
“…To meet the increasing demand for eco-friendly, renewable, and portable/mobile power sources, researchers have continued to study new energy conversion and storage systems [1][2][3][4][5]. Zn-air batteries have been widely studied owing to their high theoretical energy density, excellent safety, and eco-friendliness compared to other types of rechargeable batteries [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In tetragonal λ‐MnO 2 , Zn 2+ diffuses from 8a‐sites to neighboring 8a‐sites through 16c‐sites; however, Mn atoms at 16d‐sites (close to 16c‐sites) hinder the movement of Zn 2+ by electrostatic repulsion 81 . These findings confirm that further architecture modification is necessary for spinel‐type samples like λ‐MnO 2 and ZnMn 2 O 4 to become qualified Zn 2+ hosts considering their limited 3D tunnels and strong electrostatic repulsion toward Zn 2+ 26,38,39,48,67 . As shown in Figure 6, a treatment on the ZnMn 2 O 4 lattice was carried out to produce Mn vacancies or deficiencies by extracting oxygen anions, which lowers the electrostatic barrier for Zn 2+ transfer and alleviates the Mn species dissolution due to the higher Mn oxidation state.…”
Section: Crystal Structures Of Manganese Oxidesmentioning
confidence: 54%
“…Various strategies including additives addition, surface engineering, and structural/hierarchical design have been developed to circumvent these problems 41,42,45‐54 . More studies on anode modifications for ZIBs can be found in recent reviews 39,41,42,48 …”
Section: Introduction Of Flexible Zn‐ion Batteriesmentioning
confidence: 99%